Crisis in South Korea: From Social Theory to Practices - Pamungkas, Cahyo (RMPI-BRIN, 2017)
This article aims at describing the way the dimension of the social crisis is within the social sciences and humanities discourses, and the extent such a dimension is noticeable within the crisis reality in South Korea. Literature study of crisis for this study indicates that social crisis is, in theory, a general failure occurring in social life within a historical period, such a crisis produces collective distress generated by the incongruity between the ideas structure and the material structure. The crisis dimension consists of socio-political and socio-economic crisis and natural disasters. Available data on the socio-political crisis reality in South Korea displays a fact that those theoretical dimensions are discernible within the Korean society's life since their colonial era until today.